Student behavior toward the counterfeit of luxury products / Wan Ahmad Hakim Mohd Idros and Nurul Amanina Abdul Manaf - Mohd Idros, Wan Ahmad Hakim; Abdul Manaf, Nurul Amanina (Faculty of Business and Management, 2016)
Counterfeit is now the major global economy problem that needs to face by every country whether developing or developed countries. Malaysia is not spared from this global economy problem and this research is about to study whether external factors (price, product, and advertisement) affect the student behavior of UiTM toward the counterfeit luxury products. Mostly this legal activity is targeting luxury products such as handbag, shoes, clothes, watches, and gadget where all these products have big market demand. Many big companies need to bear billion dollars of lost from this counterfeit activity such as Adidas, Gucci, Apple, Aldo, and other famous brands name. One of the victim or buyers of this counterfeit luxury product is the student. This generation-Y nowadays is easy to influence by irresponsible peoples. Therefore, a research has been conducted to study the student behavior toward the counterfeit luxury product. The results of this study we will understand why the counterfeit luxury product is famous among student.